0.22(x+9)=0.2x+3.6

Simple and best practice solution for 0.22(x+9)=0.2x+3.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.22(x+9)=0.2x+3.6 equation:


Simplifying
0.22(x + 9) = 0.2x + 3.6

Reorder the terms:
0.22(9 + x) = 0.2x + 3.6
(9 * 0.22 + x * 0.22) = 0.2x + 3.6
(1.98 + 0.22x) = 0.2x + 3.6

Reorder the terms:
1.98 + 0.22x = 3.6 + 0.2x

Solving
1.98 + 0.22x = 3.6 + 0.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.2x' to each side of the equation.
1.98 + 0.22x + -0.2x = 3.6 + 0.2x + -0.2x

Combine like terms: 0.22x + -0.2x = 0.02x
1.98 + 0.02x = 3.6 + 0.2x + -0.2x

Combine like terms: 0.2x + -0.2x = 0.0
1.98 + 0.02x = 3.6 + 0.0
1.98 + 0.02x = 3.6

Add '-1.98' to each side of the equation.
1.98 + -1.98 + 0.02x = 3.6 + -1.98

Combine like terms: 1.98 + -1.98 = 0.00
0.00 + 0.02x = 3.6 + -1.98
0.02x = 3.6 + -1.98

Combine like terms: 3.6 + -1.98 = 1.62
0.02x = 1.62

Divide each side by '0.02'.
x = 81

Simplifying
x = 81

See similar equations:

| =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= | | 7a-(3a-4)=16 | | (-3)(2)(-1)(-3)= | | 6-c=16 | | -f+300=-65 | | x^2+3xy-8x-4y= | | 14(b-955)=616 | | F(10)=2x+5 | | 3+-7=4t+7 | | 2m-1=-6m+8 | | -2+10m-10=8(3m+4)-2 | | 49=3(x-3)+4x-1+2x+5 | | 24k=8(x+6) | | 3t^2-20t=-12 | | n=18+m | | 8.25c+12(55-c)=585 | | -5=7+3y | | 6x-13=83 | | 3+-7=4(t+7) | | x^2+x+120=0 | | 3x+50=275 | | -6(-6r+2)=-40+8r | | x+a^4=81a^4 | | F(n)=2n+2 | | 8d=7d-1 | | -1(1-5n)-4(-5n-2)=-18 | | x=x-50 |

Equations solver categories